Current practice of thoracic anaesthesia in Europe – a survey by the European Society of Anaesthesiology Part I – airway management and regional anaesthesia techniques - Jerome Defosse (BMC, 2021)
Abstract Background The scientific working group for “Anaesthesia in thoracic surgery” of the German Society of Anaesthesiology and Intensive Care Medicine (DGAI) has performed an online survey to assess the current standards of care and structural properties of anaesthesia workstations in thoracic surgery. Methods All members of the European Society of Anaesthesiology (ESA) were invited to participate in the study. Results Thoracic anaesthesia was most commonly performed by specialists/board-certified anaesthetists and/or senior/attending physicians. Across Europe, the double lumen tube (DLT) was most commonly chosen as the primary device for lung separation (461/ 97.3%). Bronchial blockers were chosen less frequently (9/ 1.9%). Throughout Europe, bronchoscopy was not consistently used to confirm correct double lumen tube positioning. Respondents from Eastern Europe (32/ 57.1%) frequently stated that there were not enough bronchoscopes available for every intrathoracic operation. A specific algorithm for difficult airway management in thoracic anaesthesia was available to only 18.6% (n = 88) of the respondents. Thoracic epidural analgesia (TEA) is the most commonly used form of regional analgesia for thoracic surgery in Europe. Ultrasonography was widely available 93,8% (n = 412) throughout Europe and was predominantly used for central line placement and lung diagnostics. Conclusions While certain „gold standards “are widely met, there are also aspects of care requiring substantial improvement in thoracic anaesthesia throughout Europe. Our data suggest that algorithms and standard operating procedures for difficult airway management in thoracic anaesthesia need to be established. A European recommendation for the basic requirements of an anaesthesia workstation for thoracic anaesthesia is expedient and desirable, to improve structural quality and patient safety.